2015
DOI: 10.15171/ijhpm.2015.200
|View full text |Cite
|
Sign up to set email alerts
|

Policies and Processes for Social Inclusion: Using EquiFrame and EquIPP for Policy Dialogue Comment on "Are Sexual and Reproductive Health Policies Designed for All? Vulnerable Groups in Policy Documents of Four European Countries and Their Involvement in Policy Development"

Abstract: The application of EquiFrame in the analysis of sexual and reproductive health policies by Ivanova et al to a new thematic area, their selection of only some of the Core Concepts of human rights in health service provision and the addition of new vulnerable groups relevant to the purpose of their analysis, are all very welcome developments. We also applaud their application of EquiFrame to policies in countries where it has not previously been used, along with their use of interviews with policy-makers to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…The overarching theme revealed positive aspects regarding SRHR related issues for young people with ID such as a growing acceptance among the staff themselves and in society as a whole. This is a promising result and in line with other studies [18,19] indicating that the common rights stipulated by the UN (2006) are increasingly respected. However, the theme also points towards remaining challenges such as frustration, uncertainty and stigma, which previous studies also have shown [20,21].…”
Section: Discussionsupporting
confidence: 89%
“…The overarching theme revealed positive aspects regarding SRHR related issues for young people with ID such as a growing acceptance among the staff themselves and in society as a whole. This is a promising result and in line with other studies [18,19] indicating that the common rights stipulated by the UN (2006) are increasingly respected. However, the theme also points towards remaining challenges such as frustration, uncertainty and stigma, which previous studies also have shown [20,21].…”
Section: Discussionsupporting
confidence: 89%
“…60 Government programs to address disability must also take into account issues such as poverty which blight communities of persons with disabilities. Furthermore, since attitudes underpin most of the barriers, a comprehensive disability advocacy strategy that targets social institutions should be a fundamental element of any implementation plan.…”
Section: Resultsmentioning
confidence: 99%
“…11 Yet, we argue again, that this is not only a shortcoming of those four countries, but of most countries in the broad European region. Furthermore it is neither a shortcoming that applies solely to the vulnerable but to most.…”
mentioning
confidence: 68%